Criações neológicas no cenário político brasileiro nas eleições de 2018 e 2022. - AMORIM, Lucas Wallace Menezes (2024)
This article aims to describe the meanings of the main neologisms created in the 2018 and 2022 Brazilian elections, based on linguistic theories focused on lexicology, and, for the research to have a theoretical basis, the authors are considered Alves (2003), Correa and Almeida (2012). The work lists and analyzes some of the new lexical constructions related to right and left movements that, by bringing together extremist followers, caused political (affective) polarization in Brazil. From the analyses, it was concluded that new terms created in political contexts tend to be permeated with ideological convictions linked to the praise or depreciation of candidates and movements, which demonstrates support or disapproval towards them, in addition, they highlight the morphological and semantics that the language has to change.